Factor VII: its Turnover Rate and its Possible Role in Thrombogenesis - Loeliger, E. A; Esch, B. v. d; ter Haar Romeny-Wachter, C. Ch; Booij, H. L (Thrombosis and Haemostasis, 1960)
The range of the hourly turnover rate of factor VII, found in 17 normal individuals, 14 patients with thrombo-embolic diseases and 3 patients with congential hypoproconvertinaemia, was 11.1—16.6% of the total body pool of factor VII (mean normal value 13.8%). The possible significance of this rapid turnover rate of factor VII in prophylactic anticoagulant treatment with 4-hydroxycoumarin derivatives is stressed.